Analysis of the Impact of Tax Amnesty Policy Repetition on Tax Compliance and State Revenue in Indonesia - Rosidah, Naely Salamatun; W, Irwan Sutirman (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the impact of a repeatedly implemented tax amnesty policy on the level of tax compliance and state revenue in Indonesia. Tax is the main source of state revenue and plays a crucial role in funding development and public services. However, low tax compliance is a serious challenge for the national tax system. The Indonesian government has implemented tax amnesty several times as an effort to improve compliance and broaden the tax base. Although this policy provides short-term benefits in the form of increased revenue. Research results show that repeating tax amnesty can actually reduce long-term tax compliance and create negative expectations among taxpayers. Taxpayers tend to postpone their obligations in the hope that there will be another tax amnesty, which ultimately has a negative impact on the stability of state revenues.